Ultrasound physics and technology : how, why and when - Gibbs, Vivien; Cole, David; Sassano, Antonio (Churchill Livingstone/Elsevier, 2009)
Written for health practitioners and students new to medical ultrasound, this book provides various basic physics and technological knowledge they need in order to practise ultrasound, including safety aspects of ultrasound, quality assurance and the techniques and developments.